Closing the Loop: Goal Programming-Based Optimization in a Tofu-Centered Agro-Eco-Industrial Park - Putri, Ade Aisyah Arifna; Purwaningsih, Ratna; Azzahra, Faradhina; Hartini, Sri; Irawan, Candra; Oryzanti, Parwa (Spektrum Industri, 2025)
Developing an agro-eco-industrial park based on the tofu industry must consider the balance of each agro-industry's production capacity. This research aims to (1) develop an optimization model for material flow between industries and (2) explain the material flow and provide waste utilization recommendations for other industries to create a closed loop. The industries involved in this agro-eco-industrial park consist of the tofu industry, fertilizer producers, tempeh gembus producers, cattle farms, biodigesters, paddy farmers, soybean producers, and nata de soya producers. The model was created using a goal programming approach. Traditional tofu processing generally generates a variety of waste with high nutritional value, but it is detrimental to the environment if disposed of directly. The flow of materials among the related industries is based on the tofu industrial cluster, which consists of 30 industries in Grobogan, Central Java, Indonesia. The expected output comprises eight decision variables representing the production amount of industries. Data analysis reveals that the model outperforms the current conditions, with the waste recycling rate increasing from 14 % to 97 %. This model converts waste into valuable resources such as fertilizer and gas energy through biodigester processing and other economically viable methods.